Congratulations to FSG researchers at ITEX'21 - UiTM, Faculty of Applied Sciences (Faculty of Applied Sciences, 2021)
Congratulations to all winners at the 32nd International Invention, Innovation, and Technology Exhibition (ITEX’21)